APPLICATION OF BORROWING AND RETURN THE BOOK IN LIBRARY AZZIRA USING MICROSOFT VISUAL BASIC 6.0. - Soraiya Alattas; Erick Orlando, SKom, MMSI (Jurnal Sistem Informasi, 2010)
This paper describes the writing on the application and loaning return library books inAzzira during this process is done manually. Therefore the writer create a transactionsystem with computerize transactions using a programming language MicrosoftVisual Basic 6.0 and Databases using Microsoft Access.Hopefully this writing has become an alternative for the library or to its employeeswho expect all current activities with effective, efficient and coordinated.